2016
DOI: 10.2460/javma.249.11.1308
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variability of Demodex cati in a feline immunodeficiency virus-positive cat

Abstract: CASE DESCRIPTION A 17-year-old FIV-positive cat was evaluated because of weight loss during the preceding few months. The cat had a weight loss of 0.5 kg (1.1 lb) during the last month. Because of its FIV-positive status, the cat was confined indoors. CLINICAL FINDINGS A large nonpruritic area of alopecia with hyperpigmentation and comedones was present on the right lateral aspect of the neck. The chin had diffuse alopecia and comedones. Mild alopecia was present on the dorsal aspect of the muzzle. Trichograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…Despite the morphological differences observed in the mites found in the present study, it is not possible to claim that the case described here consisted of co-infection between D. cati and D. gatoi. Taffin et al (2016) demonstrated in their study that mite morphology can be affected by the host's immune status. These authors noticed mites with different morphological presentations in a single animal and initially believed that their case involved co-infection between D. cati and D. gatoi.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the morphological differences observed in the mites found in the present study, it is not possible to claim that the case described here consisted of co-infection between D. cati and D. gatoi. Taffin et al (2016) demonstrated in their study that mite morphology can be affected by the host's immune status. These authors noticed mites with different morphological presentations in a single animal and initially believed that their case involved co-infection between D. cati and D. gatoi.…”
Section: Discussionmentioning
confidence: 99%
“…Females had a total length of 219.0 ± 27.4 µm, with the gnathosoma measuring 16.2 ± 1.9 µm, the podosoma 58.7 ± 2.6 µm and the opisthosoma 143.9 ± 25.4 µm. Values of 181.7 ± 17.9 µm (males) and 219 ± 27.4 µm (females), representing the total length were reported by Taffin et al [7]. Smaller sizes, respectively 170.8 ± 1.4 µm (gnathosoma 24.3 ± 0.8 µm, podosoma 58.2 ± 0.9 µm, opisthosoma 88.4 ± 0.5 µm) [8] and 140-175 µm [7], representing the total length, were noticed in Demodex spp.…”
Section: Resultsmentioning
confidence: 54%
“…Values of 181.7 ± 17.9 µm (males) and 219 ± 27.4 µm (females), representing the total length were reported by Taffin et al [7]. Smaller sizes, respectively 170.8 ± 1.4 µm (gnathosoma 24.3 ± 0.8 µm, podosoma 58.2 ± 0.9 µm, opisthosoma 88.4 ± 0.5 µm) [8] and 140-175 µm [7], representing the total length, were noticed in Demodex spp. males.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations